Pancasila-Based Neutral Center as a Global Conflict Peace Catalyst and Conflict Resolution - Andi Nur Oktafiana; Wilda Rizkiya; Arik Cahyani (Indonesian Student Association Study Center in Türkiye, 2025)
In the face of geopolitical instability and ongoing international conflicts, the concept of a